Functional outcome and cost effectiveness of patellar resurfacing and non-resurfacing in total knee arthroplasty: systematic review and meta-analysis - Muhammad Andry Usman; Henry Yurianto; Nur Rahmansyah; St.Fatimah Zahrah Anwar (Journal of Orthopaedic Surgery and Research)
Abstract Background Total knee arthroplasty (TKA) is rising globally, with patellar management impacting outcomes. Resurfacing reduces pain and revision rates but poses complications, while non-resurfacing lowers costs but risks persistent pain. This study updates previous meta-analyses by comparing the functional and economic outcomes of both approaches. Methods This systematic review and meta-analysis followed PRISMA guidelines. Studies comparing patellar resurfacing and non-resurfacing in TKA with functional outcomes in adults were included. Five databases were searched until February 6, 2024. Two authors independently extracted data and assessed risk of bias. Any disagreements were resolved by a third author. Statistical analysis used a random-effects model, reporting mean differences (MD) and odds ratios (OR) with 95% CI. Sensitivity and subgroup analyses were performed to assess heterogeneity and reliability. Results A total of 49 studies (34 RCTs, 15 observational) were included from 963 screened records. Analysis of 22 studies found no significant difference in Knee Society Score (KSS) function between resurfacing and non-resurfacing (MD 2.03; 95% CI 0.58–3.48; p = 0.59, I2 = 53%). Resurfacing significantly reduced anterior knee pain (OR 0.61; 95% CI 0.42–0.87; p = 0.007, I2 = 70%). However, no significant differences were observed in pain scale, range of motion (ROM), or Oxford Knee Score. Three studies assessed economic outcomes using Incremental Net Benefit (INB) and Incremental Cost-Effectiveness Ratio (ICER) showed no significant cost-effectiveness. Conclusions Patellar resurfacing in TKA significantly reduces anterior knee pain but shows no advantage in KSS function, pain scale, Oxford Knee Score, ROM, or cost-effectiveness. Surgical decisions should be individualized to optimize patient outcomes.